The limited modesty of subsidiarity - Barber, N (Blackwell Publishing, 2005)
This paper provides an account of the European principle of subsidiarity that presents it as a principle of democratic structuring: engaging both with the allocation of powers to existing democratic institutions and with the creation of new democratic institutions. In the process of discussing the European principle, a contrast is drawn with the Catholic principle of subsidiarity and with the rival doctrine of national self-determination. It is argued that the European principle is a central part of the Union's constitutional identity, and, as such, crucial to an understanding of the European project.